Best leadership practices of nurses in hospital risk management: case study - Mônica Emanuele Köpsel Fusari; Betina Hörner Schlindwein Meirelles; Gabriela Marcellino de Melo Lanzoni; Veridiana Tavares Costa (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To highlight the best leadership practices of nurses who contribute to hospital risk management. Method: Single case study with two integrated units of analysis, with a qualitative approach. Data collected from April to November 2018, through focused interviews with nurse managers, non-participant observation and documentary research. Analysis using the analytical technique to the explanation construction. Results: Three thematic categories were evidenced, demonstrating that the best leadership practices involve technical and non-technical competencies anchored in behavioral development, scientific knowledge, guidelines for quality and patient safety and participatory management of the health team. Conclusion: The best leadership practices of nurses who contribute to hospital risk management pervade technical skills and/or formal positions, valuing each team professional in a unique way and emphasizing the importance of scientific knowledge and the professional reference model that the nurse exercises in hospitals.